Green building and policy innovation in the US Low-Income Housing Tax Credit programme. Issue 5 (4th July 2021) - Yeganeh, Armin; McCoy, Andrew P.; Reichard, Georg; Schenk, Todd; Hankey, Steve
ABSTRACT: This article analyses the integration of green building with the largest low-income housing production programme in the US and the innovativeness of state housing agencies. Drawing on policy innovation literature, panel data and regression analysis are employed to quantify associations between state-level characteristics and the adoption of green building criteria into the Low-Income Housing Tax Credit (LIHTC) programme. Results show that housing agencies have increasingly adopted green building criteria, and most have identified co-benefits from energy-efficient buildings and smart growth. Despite overall progress, the rate of adoption of green building criteria has decreased, few US states have comprehensive criteria, and many have dropped important criteria, such as on-site renewable energy generation, often due to perceived additional costs to developers and, in some cases, due to perceived progress in building codes. Results are consistent with hypotheses derived from the literature and suggest that the integration of green building with the LIHTC programme is significantly associated with the states' internal factors, such as public housing agencies' motivations and resources, and external factors like regional policy diffusion from other states. Future research should explore organization-level factors that affect environmental policy innovation.